Increased mean R2* in the deep gray matter of multiple sclerosis patients: Have we been measuring atrophy?. Issue 1 (4th December 2018) - Hernández‐Torres, Enedino; Wiggermann, Vanessa; Machan, Lindsay; Sadovnick, A. Dessa; Li, David K.B.; Traboulsee, Anthony; Hametner, Simon; Rauscher, Alexander
Abstract : Background: Magnetic resonance relaxometry studies in multiple sclerosis (MS) have suggested that iron accumulates within deep gray matter (DGM) structures early in the disease course. However, the commonly utilized mean R2* and magnetic susceptibility measures reflect regional iron concentration but not a structure's total iron content. Thus, tissue atrophy could impact mean R2* and magnetic susceptibility estimates. Purpose: To demonstrate that both average iron concentration and total iron content need to be reported in order to distinguish between atrophy‐related and definite magnetic susceptibility changes. Study Type: Observational. Population: The study was performed on 30 healthy controls (HCs) and 39 people with definite MS. Field Strength/Sequence: 3T Philips Achieva using an 8‐channel SENSE head coil. R2* data were acquired using a multiecho gradient echo sequence and diffusion tensor imaging data were acquired using an echo‐planar sequence. Assessment: Total iron content in DGM structures was assessed by calculating the sum of all R2* values within a region (denoted as R 2 m a s s * ) and compared to the mean R2* as a measure of iron concentration. Statistical Test: Significant group differences were investigated in a linear regression model. All DGM structures were assessed individually and the significance threshold was adjusted using the Bonferroni‐Holm correction for multiple comparisons. Results: There was an increased mean DGM R2* in MS patients compared to HCs (significant in the pallidus, P = 0.0051). In contrast, R 2 m a s s * in patients was found to be lower in the thalamus and the caudate ( P = 0.0011) compared to HCs, and similar between the two cohorts in the other DGM regions. Data Conclusion: An increase in mean R2* may not necessarily reflect increased iron accumulation. We propose R 2 m a s s * as an additional metric to account for the effects of tissue atrophy when assessing tissue content changes, such as iron deposition or loss. Level of Evidence: 1 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2019;50:201–208.